Analisis Pengereman dinamik pada Motor Induksi 3 Fasa dengan metode Injeksi Arus Searah dan Kapasitor Eksitasi Sendiri Fuzzy C-Means Clustering - Ri Munarto; Bobby Rinaldi (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2018)
Induction motors are used in many industrial production processes because of their robustness, high reliability and efficiency, low cost, and good self starting. In a vast number of industrial applications and drives, a very important requirement is for motor to be able to be quickly sttoped. This is also very necessary to save machine parts and prevent injuries to the people in the vicinity in case a fault occurs. This means that good braking techniques are needed which are able to efficiently remove the kinetic energy of the motor. From experiment using MATLAB Simulink R2014b with DC injection using 22 V and 110 V, found that 110 V DC inject have braking time 0.61 second without load and 0.46 second with load 4,29 N.m, beside that capacitor self excitation with capacitor 1000 μF have braking time 29.16 second without load and 6.08 with load 4,29 N.m, so it can be found solution that DC inject the most effectif braking